The influece of the trading volume, dividend yields, and price earnings towards the stock returns in Malaysia / Haslinda Othman - Othman, Haslinda (Bachelor Of Business Administration (Hons) Marketing, 2013)
The purpose of this study is to investigate the influence of trading volume, dividend yields and price earnings towards the stock returns on public listed companies in Malaysia. There are 102 public listed companies selected randomly from Bursa Malaysia main market. The period of the present study is from from January 2007 until December 2009.The data has been collected from various sectors such as consumer, industrial, construction, plantations, infrastructure, real estate, trading and services and REITS. Stock return has been chosen as a dependent variable. While trading volume, dividend yields and price earnings have been chosen as an explanatory variables in this study. Based on the findings ,there are only one explanatory variables which is dividend yield that is significant towards stock returns. The other two explanatory variables, price earnings and trading volume are insignificant. In short, the study found that stock return can be explained by dividend yield for the period of 2007 until 2009